Modeling the Scheduling of Berth and Quay Crane During the Unloading Process at Lattakia International Container Terminal - يوسف, أيمن; سلوم, تمام; دشر, شاديه (Latakia University Journal -Engineering Sciences Series, 2021)
This study examines the integration between the problems of allocating berths and quay cranes, with a focus on the process of unloading a ship at the container port. A study of 10 voyages for one ship was selected only, and special mathematical models were developed for each criterion studied (berth - berth cranes). The genetic algorithm was proposed as a methodology for solving these models and applying them to the Matlab 2016 program that gives the optimization solved by the studied allocation process within Container port at the port, which aims to reduce ship berthing time. These experiments showed that the solution algorithm can efficiently handle the scheduling problem, and the computational results of the model and the solution method proposed in this article have shown its effectiveness in solving the integrated unloading problem of the container terminal.